2017
DOI: 10.1016/j.cub.2016.11.037
|View full text |Cite
|
Sign up to set email alerts
|

A PP2A-B55-Mediated Crosstalk between TORC1 and TORC2 Regulates the Differentiation Response in Fission Yeast

Abstract: SummaryExtracellular cues regulate cell fate, and this is mainly achieved through the engagement of specific transcriptional programs. The TORC1 and TORC2 complexes mediate the integration of nutritional cues to cellular behavior, but their interplay is poorly understood. Here, we use fission yeast to investigate how phosphatase activity participates in this interplay during the switch from proliferation to sexual differentiation. We find that loss of PP2A-B55Pab1 enhances the expression of differentiation-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 49 publications
(64 reference statements)
2
51
0
9
Order By: Relevance
“…We found that TORC1 controls SAGA through Ppk18 Gwlmediated inhibition of the PP2A B55 phosphatase. A very recent study proposed that a similar TORC1-activated signaling cascade inhibits sexual differentiation, through the de-phosphorylation of Gad8 AKT by PP2A B55 , thereby counteracting TORC2 activity [56]. Our work reveals that an additional substrate of the TORC1-PP2A B55 pathway contributes to control this process.…”
Section: Embo Reportssupporting
confidence: 59%
See 1 more Smart Citation
“…We found that TORC1 controls SAGA through Ppk18 Gwlmediated inhibition of the PP2A B55 phosphatase. A very recent study proposed that a similar TORC1-activated signaling cascade inhibits sexual differentiation, through the de-phosphorylation of Gad8 AKT by PP2A B55 , thereby counteracting TORC2 activity [56]. Our work reveals that an additional substrate of the TORC1-PP2A B55 pathway contributes to control this process.…”
Section: Embo Reportssupporting
confidence: 59%
“…Interestingly, an S. pombe FOXO transcription factor, Fkh2, is also required for ste11 + induction and sexual differentiation upon nitrogen starvation [64] and is phosphorylated by Gad8 AKT in vitro [39]. Recently, a mutational analysis revealed that Gad8 AKT -dependent phosphorylation of Fkh2 is critical for sexual differentiation [56]. Our results show that Taf12 phosphorylation is induced early upon starvation, positively correlates with TORC2 activity, but not any other nutrient-sensing pathway, and negatively correlates with sexual differentiation.…”
Section: Embo Reportsmentioning
confidence: 99%
“…These mutants are unable to cease cell growth, arrest with 1C DNA and sustain viability after nitrogen withdrawal (Sajiki et al, 2009;Sajiki, Tahara, Villar-Briones et al, 2018). TORC2 and Gad8, a downstream effector kinase of TORC2, were also reported to be required for cells to arrest with 1C DNA under −N and sexual differentiation (Ikeda, Morigasaki, Tatebe, Tamanoi, & Shiozaki, 2008;Martin et al, 2017;Matsuo, Kubo, Watanabe, & Yamamoto, 2003). Inhibition of PP2A Pab1 through the Ppk18/Cek1-Mug134 pathway may contribute to maintaining the state of phosphorylation of some substrates of these kinases which is important for proper entry into the G 0 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of TORC1 triggers the mating response [83,84], while deletion of TORC2 or its target Gad8 (the fission yeast orthologue of mammalian Akt) causes sterility [85]. Recently, it has been shown that the transition from cell growth to cell differentiation in response to nitrogen starvation, is regulated by PP2A/B55 phosphatase activity [38] through the dephosphorylation of Gad8 at Ser546 [37,82,86]. As indicated above, in low nitrogen, TORC1-Sck2 inactivation leads to the activation of the Greatwall-Endosulfine switch and therefore the inhibition of PP2A/B55, resulting in the accumulation of active Ser546 phosphorylated Gad8 and induction of the differentiation response.…”
Section: Pp2a/b55 Connects Torc1 and Torc2 And Provides A Switch Frommentioning
confidence: 99%
“…In Saccharomyces cerevisiae, TORC1 and protein kinase A (PKA) activities inhibit the Greatwall-Endosulfine switch, which is required for meiotic gene expression and survival in the G0 stationary phase [31][32][33][34]. By contrast, in fission yeast, the Greatwall-Endosulfine switch is negatively regulated by TORC1 [35], and it regulates cell size at division, entry into quiescence [36], and the sexual differentiation response [37,38].…”
Section: Introductionmentioning
confidence: 99%